Relentless Progress - Zipes, Jack (Taylor and Francis, 2013)
Can fairy tales subvert consumerism? Can fantasy and children's literature counter the homogenizing influence of globalization? Can storytellers retain their authenticity in the age of consumerism? These are some of the critical questions raised by Jack Zipes, the celebrated scholar of fairy tales and children's literature. In this book, Zipes argues that, despite a dangerous reconfiguration of children as consumers in the civilizing process, children's literature, fairy tales, and storytelling possess a uniquely powerful (even fantastic)capacity to resist the
Description based on publisher supplied metadata and other sources
Keywords: Kinderliteratur; Erzählen; Märchen